Dental caries in inland Brazilian adolescents and its relationship with social determinants - Andréa Videira Assaf; Angela Scarparo Caldo-Teixeira; Flavia Maia Silveira; Maria Isabel Bastos Valente; Rafael Gomes Ditterich; Roberta Barcelos (Universidade Estadual de Campinas, 2009)
Aim: To identify the prevalence of dental caries in inland Brazilian adolescents, and to analyze the influence of socio-demographic and clinical variables, and access to dental service on caries experience. Methods: This study had a non-probabilistic sample comprising 504 adolescents aged 12 years, attending public schools in the city of Nova Friburgo, mountain region of Rio de Janeiro, Brazil. The World Health Organization (WHO, 1997) criterion was used by previously calibrated examiners to report dental caries. Variables were obtained by means of a semistructured questionnaire applied to the adolescents' parents. Results: The D3 MFT mean was 1.90 and the Significant Caries (SIC) Index was 4.54, mainly represented by the carious component. Multiple logistic regression analysis revealed that parents with over 8 years of schooling (OR=0.579), absence of pain (OR=0.396) and not visiting the dentist (OR=0.270) might suggest protective factors against the disease; the possible risk factors were male gender (OR=1.982) and pain, extraction and others were reasons for consultation (OR=2.435). Conclusions: Although the prevalence of caries was slightly below the national mean, polarization of the disease was clearly observed. Education and no access to the dentist led to protection against the disease. These results may contribute to planning of oral health actions directed towards this target population for the control of caries.